VATICAN II AS AN ECCLESIAL PENTECOST - Fung, Jojo M. (Asian Horizons, 2012)
For many enthused and committed Church members and leaders around the world, the Second Vatican Ecumenical Council has been an ”ecclesial Pentecost” with a global ripple effect. It is as if all the tightly shut apertures of the Church were flung open to allow God’s Spirit to blow afresh within and purify her of the decadent energy that smothers the Church for centuries. The mighty wind of God’s Spirit has infused energy and life into those fossilized structures and enkindled the rank and file of the Church with intellectual vigour and pastoral zeal. The factors that occasioned this historic event remind us of the unpredictable ways of God’s omnipresent Spirit. The dynamism of this august event is still being felt in the ecclesial movements such as the basic ecclesial communities in the different local Churches.